MEMBANGUN NILAI POSITIF PADA ANAK DINI MELALUI KEGIATAN FUNCOOKING DI TK DHARMA KARTINI 2 CIMAHI - Hia, Bhineka; Sarumpaet, Nora; Rohmalina, Rohmalina (IKIP Siliwangi, 2019)
Building positive values in children early on is a process of giving guidance to learners to become human beings who have a good personality physically and spiritually. Planting the value of the character is very important applied early, through the process of integrated learning activities that will make early childhood trained to become a person who has a positive value. Learning activities provided through diverse and creative learning activities will encourage children to learn happily, and foster positive attitude values. Activities to introduce children to real activities will foster attitudes and skills in accordance with their growth and development. One of them is through simple cooking activities that are fun for the child (fun cooking).